Market Potential and Regional Disparities in Europe - Annekatrin Niebuhr (European Regional Science Association (ERSA), 2003)
A basic result of new economic geography models is that the proximity to consumer markets impacts wages and employment within regions. While there is a bulk of theoretical literature on new economic geography related empirical tests are still scarce. The present paper aims at providing some evidence on the validity of the forces emphasised by new economic geography models. The empirical analysis focuses on the relationship between the market potential and regional development in Europe. Consumers and purchasing power are unevenly distributed across space. The study analyses the significance of the market potential for the development of a cross section of European regions taking into account the effects of national borders as well. In the course of integration the significance of borders as impediments to trade and factor mobility declines presumably affecting the market potential especially in border regions. The regression analysis covers the period between 1975 and 1998.
Keywords: 330